2013
DOI: 10.1111/febs.12257
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the interactions of selected antibiotics and their Cu2+ complexes with the antigenomic delta ribozyme

Abstract: The interactions of selected antibiotics with the trans-acting antigenomic delta ribozyme were mapped. Ribozyme with two oligonucleotide substrates was used, one uncleavable with deoxycytidine at the cleavage site, mimicking the initial state of ribozyme, and the other with an all-RNA substrate mimicking, after cleavage, the product state. Mapping was performed with a set of RNA structural probing methods: Pb 2+ -induced cleavage, nuclease digestion, and the selective 2′-hydroxyl acylation analyzed by primer e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Binding Zn(II) to Calcitermin increases the positive charge and facilitate the interactions with negatively charged bacterial membranes [ 251 ]. A similar effect can be observed in zinc(II)/Histidine rich glycoprotein (HRG) abundant in human plasma [ 252 ]. Histatins compose a wide group of short, cationic salivary peptides secreted by the parotid and sub-mandibular salivary gland.…”
Section: Enhancing Amps Activity With Metal Ionsmentioning
confidence: 58%
“…Binding Zn(II) to Calcitermin increases the positive charge and facilitate the interactions with negatively charged bacterial membranes [ 251 ]. A similar effect can be observed in zinc(II)/Histidine rich glycoprotein (HRG) abundant in human plasma [ 252 ]. Histatins compose a wide group of short, cationic salivary peptides secreted by the parotid and sub-mandibular salivary gland.…”
Section: Enhancing Amps Activity With Metal Ionsmentioning
confidence: 58%
“…The dsDNA templates for the in vitro transcription of the transacting antigenomic HDV ribozyme were prepared as described. 22 Briey, two DNA oligomers were synthesized: A, 5 0 -GAAAAGTGGCTCTCCCTTAGCCATCCGAGTGCTCGGATGCCC AGGTCGGACCGCGAGGAGGTGGAGATGCCC-3 0 and B, 5 0 -TAA-TACGACTCACTATA GGGCATCTCCACC-3 0 (the complementary sequences are underlined in both oligomers and the letters in italics mark the T7 RNA polymerase promoter). Equimolar amounts of both oligomers A and B were annealed.…”
Section: Dna Template Constructmentioning
confidence: 99%
“…We have previously found that the inhibitory properties of some antibiotics signicantly increase when complexed with Cu 2+ , so the impact of Cu 2+ -antibiotic complexes on ribozyme activity was also analyzed. [21][22][23][24] We were curious to know whether Cu 2+ ions might inuence the application of the uorescence-based assay.…”
Section: Impact Of Selected Antibiotics and Their Complexes With Cu 2...mentioning
confidence: 99%
See 1 more Smart Citation
“…Aminoglycoside‐binding sites have been identified in rRNA [7,16], HIV trans‐activating region [17], Rev responsive element [18] and autocatalytic ribozymes [19]. Aminoglycosides can enhance hairpin ribozyme activity in the absence of metal ions [20], and they inhibit hammerhead and hepatitis delta virus ribozyme self‐cleavage through direct interactions with the RNA [21–23]. Small doses of tobramycin induce biofilm formation by targeting a putative cyclic diguanosine monophosphate phosphodiesterase associated with cell surface adhesion in Pseudomonas aeruginosa and in Escherichia coli [24].…”
Section: Introductionmentioning
confidence: 99%